1975
DOI: 10.2165/00003495-197510040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Fenfluramine

Abstract: Fenfluramine has been used for a number of years as a short-term adjunct to diet in the management of obesity. Controlled studies and clinical experience have shown that it possesses anorectic activity at least as good as that of other therapeutically useful drugs of its type, but like these drugs it has only a limited role in the overall management of obesity. Tolerance to the anorectic effects of fenfluramine may possibly develop more slowly than to other chemically related drugs in patients with refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(11 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…The use of allopathic and pharmacological drugs has become a popular means to overcome excess weight gain [11]. While these drugs generally are effective, severe adverse toxicities may limit their overall usefulness [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of allopathic and pharmacological drugs has become a popular means to overcome excess weight gain [11]. While these drugs generally are effective, severe adverse toxicities may limit their overall usefulness [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…3). Its major metabolite, norfenfluramine, is believed to be the main active form in humans [19]. Propylhexedrine is prepared by catalytic hydrogenation of (±)-or (-)-ephedrine in a strong mineral acid [20].…”
Section: β-Phenylisopropylaminesmentioning
confidence: 99%
“…Three doses of fenfluramine were administered to provide various circulating concentrations of fenfluramine in lean and obese mice, since steady state is influenced both by body weight and storage in adipose tissue (21). Our observation of reduced body weight only in lean mice receiving the highest dose of fenfluramine is not in agreement with the report of Bizzi et al (22), who observed that fenfluramine administered on the basis of total body weight to lean and gold-thioglucose (GTG) obese mice was more effective in reducing food intake in obese mice than in lean mice.…”
mentioning
confidence: 99%